Dramatic Enhancement of CO2 Photoreduction by Biodegradable Light‐Management Paper. Issue 16 (19th February 2018) - Wang, Yangang; Li, Tian; Yao, Yonggang; Li, Xi; Bai, Xia; Yin, Chaochuang; Williams, Nicholas; Kang, Shifei; Cui, Lifeng; Hu, Liangbing
Abstract: Photocatalytic reduction of CO2 with H2 O vapor is gaining increased interest because it is a promising "green chemistry" route for the direct conversion of CO2 to value‐added chemicals driven by solar energy. To increase the efficiency of photocatalytic conversion, most efforts are made by exploring various photocatalysts while little effort on advanced light management. For the first time, it is demonstrated that bio‐degradable transparent paper with excellent light diffusivity can effectively enhance the light utilization of photocatalytic reactions when attached on the device surface, and thus greatly increase the conversion efficiency. As a proof‐of‐concept, a graphitic carbon nitride (g‐C3 N4 ) photocatalyst with transparent paper attached, exhibited 1.5 times higher photocatalytic activity than bare g‐C3 N4 in the reduction of CO2 under visible light irradiation. The improved catalytic performance can be ascribed to the (1) refractive index matching and (2) enhanced light absorption via prolonged light traveling path in transparent paper, which decreases the light reflection at surface and traps the absorbed light inside, leading to an increased light absorption at the active layer of the device. The transparent paper with a controllable light management behavior has an unprecedented potential for applications in photocatalysis as a general method for improved light utilization. Abstract : A biodegradable transparent paper with a high haze can be utilized as an efficient light management coating for applications in photocatalysis. An ≈50% improvement on the photocatalytic activity is achieved after coating the transparent paper on the surface of a g‐C3 N4 photoactive layer in the reduction of CO2 with H2 O vapor under visible light irradiation.